Centrality of Self in Saiva Siddhanta - Vanchipura, Vipin Varghese (Journal of Dharma, 2008)
V. S. George Joseph, Centrality of Self in Saiva Siddhanta, Bangalore: Asian Trading Corporation, 2006, pages: 263, ISBN: 81-70863-68-6.